ҚАРАҚАЛПАҚСТАНДА РАЙОНЛАРДЫҢ ДҮЗИЛИЎ ТАРИЙХЫНАН - Есназарова, З.Б. (SCIENCE and SOCIETY, 2023)
This article is about the history of the development of the regions of Karakalpakstan. The article considers the main approaches to the study of the processes of formation and development of cities and regions. Cities and regions were studied as a separate phenomenon on the basis of modern programs. Based on the experience of foreign researchers, the article compares different stages of the study of cities and regions, and identifies the main directions for the development of cities and regions. Cities were considered as a socio-cultural phenomenon, including various systems and practices of everyday life. The article deals with topical is- issues, the processes of forming relations between cities and districts in the context of the emergence of new districts and cities, the way of life, the values of citizens, the development and location of cities such as Turtkul, Beruniy, Chimbay, Shumanai, Kegeyli, Takhiatash, Khodjeli, studied demography relating to the XXth century.